TUGAS DAN TANGGUNG JAWAB KURATOR DAN HAKIM PENGAWAS DALAM PEMBERESAN HARTA PAILIT - Erlan Ardiansyah; Rahmia Rachman (Fakultas Hukum Universitas Hang Tuah, 2021)
Duties and responsibilities of curators and supervisory judges in the enactment of bankruptcy property under Law Number 37 of 2004 concerning Bankruptcy and Suspension of Payment. This research aims to find out the Duties and Responsibilities of Curators and Supervisory Judges in the enforcement of bankruptcy property when debtors sell bankruptcy property that harms creditors. This research uses Normative research methods, namely: Library research is research that uses secondary data, namely data sourced from library materials, studying various scientific writings, laws and regulations, documents and other sources related to the material discussed. The result of this research is that curators have a duty to manage and settle bankruptcy property under the supervision of supervisory judges appointed by Commercial Court Judges. Curators also have a personal responsibility if in carrying out their duties he performs kelalalian so as to cause losses to bankruptcy property. While the Supervisory Judge has a duty to supervise the curator in carrying out his duties in cleaning up the bankruptcy property. If the debtor commits a legal action on the bankruptcy hrta that harms the creditor, then the curator based on the mandate of Article 16 of the Bankruptcy Law and PKPU can file an Actio Pauliana lawsuit to the Commercial Court which aims to cancel the legal actions committed by the previous debtor so that the bankruptcy property can be maximized to be distributed to the creditors.